Kandungan emisi gas rumah kaca pada kebakaran hutan rawa gambut di pelalawan Riau - Ati Dwi Nurhayati; Ervina Aryanti; Bambang Hero Saharjo (Institut Pertanian Bogor, 2010)
Peat land in the east coast of Sumatera (Riau, Jambi, South Sumatera) and Kalimantan (South Kalimantan, Central Kalimantan and West Kalimantan) has being used for agricultural crops such as rice field, palm oil and coffee plantation. land preparation practiced is slash and burn method. Smoke haze that produce from peat fires were caused by these method. To determine the impact of such practice to atmospheric quality, a study was conducted at Pelalawan Province Riau. Four plots on peat land were prepared at sapric and hemic, each plot was 20 m x 20 m (0,04 ha). Before burning vegetation was cleared off, then the plots were circularly burned (ring fire) and greenhouse gases emitted were measured. The average of greenhouse gases emitted from sapric plot burning were 273 ppm CH[4], 10.395 ppm C0[2] and 1.223 ppm CO. Greenhouse gasses emitted from hemic plot burning were 306 ppm CH[4], 10.678 ppm C02 and 2176 ppm CO. The high CO emission from peat burning indicate there has been an incomplete burning at the fuel, due to high fuel moisture. The largest single atmospheric emission from peat burning was C0[2] and the smallest was CH[4] • The increase of greenhouse gases emission will contribute to global climate change, especially the global temperature increase through greenhouse effect of the gases.